The Attentional Bias in Current and Former Smokers - Masiero, Marianna; Lucchiari, Claudio; Maisonneuve, Patrick; Pravettoni, Gabriella; Veronesi, Giulia; Mazzocco, Ketti (Frontiers in Behavioral Neuroscience, 2019)
Scientific evidence supported the idea that cigarettes smokers suffer from an attentional bias (AB). However, contrasting data about the role of the AB on former smokers are present in literature. A multidimensional approach is needed both to collect more data about smokers’ and former smokers’ characteristics and to plan targeted interventions to help current smokers stop and former smokers remain abstinent. The main aim of this study is to investigate the presence of the AB and its effect size in smokers and former smokers. Two hundred and forty-five participants (male 50.6%; female 49.4%) aged 54.81 (SD= 14.352, range 18-63) were recruited by screening program for lung cancer. The sample of the present study consisted of 131 smokers (39.7%), 149 former smokers (45.2%) and 50 nonsmokers (15.2%). A battery of neuropsychology test (Emotional Smoke Stroop Task and Go/ no-Go task) and validated questionnaires were used (BIS-11; BIS-BAS; FTND) to define the psychological and smoking-related characteristics. Our data confirm that current smokers suffer from an attentional bias so that they show to be strongly attracted by smoking-related cues. However, also former smokers seem to be equally biased. The strength of this effect resulted seems not to be modulated by the years of current and/or previous smoking and impulsivity.